Measuring the Effect of Marketing Communication Strategy on Generating Positive Word of Mouth among the Client of the Telecommunications Sector Companies in Algeria Using Partial Least Squares Structural Equation Modelling (PLS- SEM) - بوجنانة فؤاد; الداوي الشيخ (Finance and Business Economies Review, 2021)
this study aimed to measure and analyse the effect of marketing communication strategy tools (advertising, personal communication, public relations, sales promotion, direct marketing) on generating positive word of mouth, among client of telecommunications sector companies in Algeria. we collected data from 400 clients in Mila province, using structured questionnaire, Data were analysed using partial least squares structural equation modelling (PLS- SEM), using the smart PLS 3.2.8 software, the study results show that al tools of marketing communication strategy have had a positive significant effect on generating positive word of mouth, except personal communication tool.